(untitled) (ARQUISUR Revista, 2012)
Since the objective of developing alternative strategies of projectual knowledge of socio-physical character inside of an urban development focused on the environment of man, on the premise that considers the city as a complex articulation of places (in anthropological sense), a joint strategic between following essential dimensions of place, comes under investigation social practices relating to certain groups of humans; the meanings of these practices for the groups that develop and the rest of the groups of a particular place; features that form the stage make support to social practices and the significance that these and social practices were loaded. The basic hypothesis states that: depending on configuration schema socio-physical - symbolic of articulation of these elements, or genetic scheme in place, will emerge the keys to understand whether or not, are given in a particular urban place the preconditions for developing participatory processes of urban environmental planning. Beginning in this work hypothesis underlying a possible response based on the strategic joint between: socio-physical congruence (refer to the adequacy of a specific stage for sustainable social practices deployment level) and socio-symbolic correlation (refer to the coherence between the meaning projected from different human groups of activities associated with a particular stage).